Gerenciamento de projetos em uma consultoria industrial aplicando a metodologia PMBoK - Lorenzi, Bruno César (2013)
With the rapid growth of industries and the search for management development and process improvement has motivated the creation of new methods of project management. In this context management methodology directly influence the final results expected by the organization. There are several project management methodologies, and by a research applied descriptive and comparative, are compared two methodologies of project management. The first is supported by the literature as the most comprehensive guide to project management, and the other is a methodology formulated by a consulting firm in industrial productivity management. As consulting projects are relatively small, some processes of project management literature that advocates can be grouped, or left out, due to the experience of the managers of the consulting firm. According to the literature the non-fulfillment of some steps may bring risks to the project, and consequently the final outcome. The consulting firm uses some processes advocated in the literature, not only running the studies of risks in the project.